(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
A global issue is a matter of public concern worldwide. This list of global issues presents problems or phenomena affecting people around the world, including but not limited to widespread social issues, economic issues, and environmental issues. Organizations that maintain or have published an official list of global issues include the United Nations, and the World Economic Forum